Re-imagining the History of British Abolition: The New Historical Consciousness in Winsome Pinnock’s Rockets and Blue Lights - Xiting Qiao (Theatre Academy)
Examining Winsome Pinnock’s Rockets and Blue Lights through a new-historical lens, this study aims to shed light on the theatrical intervention in the historical narrative of the British abolition, and to evaluate Pinnock's contribution to modern art and its interpretation through her attempt to highly fictionalize history. By constructing the protagonist J. M. W. Turner as an anti-hero, Pinnock places Turner back in a Victorian ethical context to question the arbitrary construction of Turner’s heroism by the complicity of discourses of art history and abolitionism. The juxtaposition of historical and social texts reflects Pinnock’s awareness of the fictional nature of historical texts, and reveals the continuing impact of the transatlantic slave trade. By restoring black voices across time and space, Pinnock reconstructs the black subjectivity in the history of abolition and in contemporary society. The play encourages readers to understand Britain’s past in a more inclusive and pluralistic way. While calling Britain to take responsibility for slavery, the play also explores the critical role of art interpretation in reassessing and reshaping historical narratives.